Research Progress on RET Fusion in Non-Small-Cell Lung Cancer - Zhao, Lu; Mei, Qingyun; Yu, Yongchao; Wang, Na; Zhang, Dou; Liao, Dongying; Zuo, Jinhui; Xie, Hongxia; Jia, Yingjie; Kong, Fanming (Frontiers in Oncology, 2022)
Great progress has been made in the treatment of driver gene-positive Non- Small Cell Lung Cancer (NSCLC) in recent years. RET fusion was seen in 0.7% to 2% of NSCLC and was associated with younger age and never-smoker status. The pralsetinib and selpercatinib for RET fusion NSCLC was recommended by the 2021 NSCLC treatment guidelines. This review outlines the research progress in the treatment of RET fusion NSCLC, identifies current challenges and describes proposals for improving the outlook for these patients.